Model Collaborative Governance Preparedness Disaster’s in Indonesia (Colgopredi) - Evi Yunita Kurniaty; Walid Musthafa Sembiring; Ira Rizka Aisyah Lubis; Maksum Syahril Lubis; Adam; Miftahul Husna Siregar (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
Indonesia is a country with a high level of disaster vulnerability, so disaster preparedness is a strategic agenda in national development. However, the complexity of disaster management often faces obstacles to coordination between stakeholders, including government, civil society, the private sector, and international organizations. This research uses the Collaborative Governance Preparedness Disaster's Model in Indonesia (COLGOPREDI) as an innovative approach in building collaborative governance-based disaster preparedness. This model emphasizes synergy across actors through the principles of participation, transparency, accountability, and strengthening local capacity. COLGOPREDI is designed to strengthen communication networks, coordination mechanisms, and a clear division of roles in the disaster management cycle, from mitigation, preparedness, emergency response, to recovery. The study results show that the implementation of this model has the potential to increase the effectiveness of disaster response, accelerate recovery, and encourage community resilience. Thus, COLGOPREDI can be a conceptual framework as well as a collaborative governance practice that is relevant in the context of disaster management in Indonesia.